2-D electron system in the RF-discharge plasma. Part II. similarity of TDES in a solid and in the RF discharge - Berezhnyj, V.L.; Berezhnaya, I.V. (Вопросы атомной науки и техники, 2019)
Comparison studies have been carried out into structural and physical peculiarities of the two-dimensional electron system (TDES) in solids and the RF plasma. The observed similarity points to possible workability and usefulness of advances in scientific and applied investigations in solids for improving the efficiency of RF plasma heating. Проведено порівняльний аналіз структурних та фізичних особливостей ДЕС у дослідженнях твердих тіл та ВЧ-плазми. Їх аналогічність вказує на можливість та корисність використання наукових та прикладних досліджень у твердих тілах для підвищення ефективності ВЧ-нагріву плазми. Проведен сравнительный анализ структурных и физических особенностей ДЭС в исследованиях твердых тел и ВЧ-плазмы. Их аналогичность указывает на возможность и полезность использования научных и прикладных достижений в твердых телах для повышения эффективности ВЧ-нагрева плазмы.